Mediastinal cystic teratoma misdiagnosed as pleural tuberculosis: A case report and review of 53 cases revealed by pleural effusion - Katoto, Patrick D. M. C.; Byamungu, Liliane N. (Clinical case reports, 2021)
Mediastinal teratoma (MT) can be misdiagnosed for a long period and revealed by fatal pleural effusion at any age. In high burden tuberculosis settings, it is important to consider MT for extra‐pulmonary tuberculosis not responding to medical treatment. Mediastinal teratoma (MT) can be misdiagnosed for a long period and revealed by fatal pleural effusion at any age. In high burden tuberculosis settings, it is important to consider MT for extra‐pulmonary tuberculosis not responding to medical treatment.